Effect of talent management practices and employee engagement on perceived sustainable competitive advantage of commercial banks in Nairobi County, Kenya - Mosong, Stephen Makewit; Komen, Joyce; Cheboi, Josephat (Nairobi Journal of Humanities and Social Sciences, 2023)
In the modern world, organizations strive to achieve success in form of sustainable competitive advantage. The demand for key position talented and committed employees is high because they help steer the organization to outdo the competition in the marketplace. The purpose of this study was to analyze the effect of talent management practices and employee engagement on perceived sustainable competitive advantage of commercial banks in Nairobi County in Kenya. Guided by resource based view theory, positivism research paradigm and explanatory research design was adopted. The target population was 3,098 employees from 42 commercial banks whereby a sample size of 354 was used. After collecting data using structured self-administered questionnaire, analysis done comprised of descriptive, correlation, factor analysis and hierarchical multiple regression analysis. The results showed a positive and significant effect of talent management practices (β=.727, p =.030<.05) and employee engagement (β=.302, p=.029<.05) on perceived sustainable competitive advantage of commercial banks in Nairobi County. The study concluded that quality level of employees' engagement, and talent management practices enhances the perceived sustainable competitive advantages in various similar working environments and society's confidence in the organization. Managers should make efforts to increase employees' perceived organizational fairness to improve their competitiveness. As a result, managers are encouraged to take a deliberate effort to promote talent management practices and employee engagement . Future researchers are expected to focus on firms in other sectors besides assessing the effect of generation Y and generation Z on talent management practices and sustainable competitive advantage.